PENGARUH MIKORIZA (MVA) TERHADAP KETAHANAN SEMAI JATI (Tectona grandis L.f) PADA TANAH REGOSOL - ARIS PURWANTO; SUSWADI SUSWADI; Haryuni Haryuni (JURNAL ILMIAH AGRINECA, 2011)
The research means effect Mycorrhyzae culture (MVA) on resistention of Jati plant from Fusarium sp in used on regosol medium. The research had done on Laboratory Protection of Plant (Disease of Plant), Green House and Demplot Farming Faculty, Tunas Pembangunan University on April until September 2007. The research used factorial methode Randomized Completely Design (RCD), with 3 factor of treatment. Factor 1:  methode of Mycorrhizae culture, (a. Kultur (Mk), b. Non Culture (Mnk)) and methode of Non Mycorrhizae culture (NM), Factor 2 : Inoculation of Fusarium (Fusarium (F) and non Fusarium (NF)), while Factor 3 : Moment of Inoculation Fusarium sp (4 week = (M1),  8 week = (M2), 12 week = (M3)) The result of research : The treatment of used Regosol soil type, different methode of breeder Mycorrhizae culture and non culture, while methode of breeder non Fusarium (control),  different time of Inoculation Fusarium sp : 4 week, 8 week, and 12 week and to combinatinon 14 treatment (R1 until R14) shown very significant on length of primer root, significant on diameter of branch, dry weight of root, but non significant on height of plant, number of leaves, wide of leaf, fresh weight of crown, dry weight of crown, number of root, fresh weight of root, and volume of root.